2020
DOI: 10.24106/kefdergi.833550
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Bilgisayar Oyun Bağımlılığı Düzeyleri ile Sorumluluk Davranışı Arasındaki İlişki

Abstract: Bilgisayar oyun bağımlılığı Ortaokul öğrencileri Sorumluluk Öz Oyun, çocuğun hayatı keşfettiği, akranlarıyla sosyal ortama katıldığı, yetenek ve bilgilerini yapılandırdığı bir faaliyettir. Geçmişte daha çok sokakta veya doğal ortamda oynanan oyunlar artık çevrimiçi ortamda oynanmaya başlamıştır. Bu çalışma ortaokul öğrencilerinin bilgisayar oyun bağımlılığı düzeylerinin cinsiyet, sınıf düzeyi, ailenin gelir düzeyi, kişisel bilgisayara sahip olma değişkenlerine göre anlamlı farklılık gösterip göstermediğini ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Research conducted by Arslan ( 2021 ) found that secondary school students’ sense of responsibility and behavior had a crucial predictive role in online gaming addiction. Another study reported a significant negative relationship between the students’ videogame addiction and their personal and social responsibility behavior (Dinçer & Kolan, 2020 ). Based on previous studies and the results of the present study, it is thought that increasing the level of responsibility of secondary and high school students would reduce gaming addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Arslan ( 2021 ) found that secondary school students’ sense of responsibility and behavior had a crucial predictive role in online gaming addiction. Another study reported a significant negative relationship between the students’ videogame addiction and their personal and social responsibility behavior (Dinçer & Kolan, 2020 ). Based on previous studies and the results of the present study, it is thought that increasing the level of responsibility of secondary and high school students would reduce gaming addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this situation, other people in the individual’s social life (e.g., family and friends) become unimportant to adolescents with low awareness of responsibility. Recent studies have observed that adolescents who excessively play videogames have difficulty fulfilling their responsibilities (Dinçer & Kolan, 2020 ; Doğan & Pamuk, 2022 ). In the present study, it was expected that adolescents with higher levels of responsibility would be less addicted to online gaming (i.e., an inverse relationship).…”
Section: Online Gaming Addiction and Basic Psychological Needsmentioning
confidence: 99%